The Impact of Experience on the Intrinsic Motivation of EFL Teachers Who Teach Online - Er, Beril; Karataş, Necmiye (Technium Social Sciences Journal, 2021)
Remote teaching has become more popular than before in Turkey as in most parts of the world because of Covid-19 pandemic. Most of the teachers and students have had some difficulties in adapting to distance education. It has been observed that the motivation of both parties might be affected by this sudden shift to online education. Although many reasons affecting teacher motivation have been identified so far, it is believed that every single study will contribute to the purpose of bettering the present EFL teaching. The current study aims to investigate the role of experience on the intrinsic motivation of EFL teachers involved in online teaching andto find out whether years of experience have an effect on teachers’ intrinsic motivation. In this study, the data was compiled from 46 EFL teachers working at Istanbul Aydin University English Preparatory School. An adapted Attitude/Motivation Test Battery (AMTB) questionnaire was used to gather the data. The obtained descriptive data were analyzed by using SPSS. The results of this study proved that experience does not have a significant impact on EFL teachers’ motivation teaching online.